Maternal methyl supplemented diets and effects on offspring health - O'Neill, Rachel J.; Vrana, Paul B.; Rosenfeld, Cheryl S. (Frontiers in Genetics, 2014)
Women seeking to become pregnant and pregnant women are currently advised to consume high amounts of folic acid and other methyl donors to prevent neural tube defects in their offspring. These diets can alter methylation patterns of several biomolecules, including nucleic acids and histone proteins. Limited animal model data suggests that developmental exposure to these maternal methyl supplemented (MS) diets leads to beneficial epimutations. However, other rodent and humans studies have yielded opposing findings with such diets leading to promiscuous epimutations that are likely associated with negative health outcomes. Conflict exists to whether these maternal diets are preventative or exacerbate the risk for ASD in children. This review will discuss the findings to date on the potential beneficial and aversive effects of maternal MS diets. We will also consider how other factors might influence the effects of MS diets. Current data suggest that there is cause for concern as maternal MS diets may lead to epimutations that underpin various diseases, including neurobehavioral disorders. Further studies are needed to explore the comprehensive effects maternal MS diets have on the offspring epigenome and subsequent overall health.